Inertially-enhanced damping energy sink for synergistic vibration-lightweight optimization in half-car suspensions - Zhang, Yuanyuan; Yan, Ronglin; Yang, Weifeng (Frontiers in Mechanical Engineering, 2025)
When applying Nonlinear Energy Sinks (NES) to vehicle suspension systems, these systems exhibit frequency sensitivity, and effective vibration reduction typically requires a relatively large mass. To address these limitations, this paper proposes an Inertially-Enhanced Damping Energy Sink (IDES). The study begins by establishing a single-degree-of-freedom vibration model to investigate the optimal configuration of the IDES. Subsequently, the effective IDES structure is applied to a half-vehicle model, and its dynamic response is solved using the Harmonic Balance Method (HBM) and the Pseudo-Arc Length Method (PALM). Under both harmonic and random excitations, the results demonstrate that the IDES significantly suppresses the resonance peak and reduces the vehicle’s vertical acceleration, as well as the dynamic deflections of the front and rear suspensions and the dynamic loads on the front and rear tires. To optimize the vehicle’s vertical and pitch angular accelerations, a genetic algorithm was employed to determine the optimal structural parameters of the IDES within the half-vehicle system. The results indicate that, compared to the NES system, the vibration reduction system with optimized IDES parameters reduces the RMS values of the vertical body acceleration by 5.56%, the front and rear suspension dynamic deflections by 9.20% and 15.56%, and the front and rear tire dynamic loads by 11.37% and 12.15%, respectively, while maintaining the pitch angular acceleration within an allowable range. Leveraging nonlinear damping and inertial mass amplification, the IDES structure overcomes the traditional NES’s dependence on cubic stiffness, offering advantages in both wide-band vibration reduction and lightweight design for vehicle suspension systems. The optimization of IDES parameters using a genetic algorithm further enhances the performance of this new damping structure. The proposed IDES structure and optimization strategy can serve as a valuable reference for the development of novel vibration damping devices in vehicles.